The 11+ Kids warm-up programme to prevent injuries in young Iranian male high-level football (soccer) players: A cluster-randomised controlled trial - Zarei, M.; Abbasi, H.; Namazi, P.; Asgari, M.; Rommers, N.; Rössler, R. (Journal of Science and Medicine in Sport, 2020)
Objective: To assess the effectiveness of the 11+ Kids warm-up programme regarding injury reduction in male high-level children`s football players.